Investigation on rejuvenation methods of aged SBS modified asphalt binder. (1st November 2020) - Cong, Peiliang; Guo, Xize; Mei, Linna
Graphical abstract: Highlights: The properties of different rejuvenated SBS modified asphalt binders were researched. The network structure of the aged SBS modified asphalt binder can be restored. The properties of asphalt binder with good network structure can be regulated in a reasonable range. Abstract: SBS modified asphalt binder (SBSMA) is widely used because of its excellent pavement performance. Recycling application for aged SBSMA has drawn increasing attention. In this study, aged SBSMA was rejuvenated with different rejuvenation methods, including the use of rejuvenator (RA), original SBSMA, base asphalt (SK-70) and original SBSMA mixed with SK-70. The conventional performance and rheological behavior of different rejuvenated SBSMA were investigated. The microscopic changes were analyzed by using Gel permeation chromatography (GPC), Fourier transform infrared (FTIR) spectroscopy and Fluorescence microscopy (FM). Results revealed that RA and original SBSMA have significant effect on the improvement of the physical-rheological and microstructures of aged SBSMA, but SK-70 did not exhibit good rejuvenation effect. The conventional tests showed that the addition of RA greatly improved the low temperature ductility and elastic recovery rate of aged SBSMA. Moreover, it was proved that RA could increase the creep compliance and improve the stress relaxation ability of aged SBSMA according to physical rheological parameters. This result indicated that RA improved the cracking resistance of aged SBSMA at low temperature. Based on the microscopic test results, it was found that RA not only could regulate the internal components of aged SBSMA, but also restore the network structure of aged SBSMA. Furthermore, the SBS polymer content indices and the softening indices are closely correlated with the performances of the rejuvenated SBSMA. From the analysis, it is necessary to rejuvenate the aged SBSMA by softening base asphalt and restoring the network structure of SBS copolymer.